Pengaruh Biaya Diklat, Jumlah Kantor, dan Jumlah Tenaga Kerja pada Laba Perbankan Syariah - Ratih Hastasari; Suharini Suharini (JMK (Jurnal Manajemen dan Kewirausahaan), 2021)
This paper analyzes how significant the internal company factors affecting the profit of the sharia banking industry. There are so many variables that can affecting profit, and profit is an important part of shariah banking for its business sustainability, so in this research, profit was selected as the dependent variable, its data was taken from monthly reports of sharia banking profit/Loss, the independent variables that were selected are the cost of education and training, the number of sharia banking offices, and the amount of the sharia banking labor. This research using 25 data starting from January 2018 to January 2020 with the results of the regression analysis indicates the difference of significance, the cost of training and education significantly affecting the profit of sharia banking, while the results of regression for the number of the office and the amount of labor indicates that both variables were not significantly affecting the profit of sharia banking.